A Method for Precision Surgical Implantation and Probe Insertion in Sprague-Dawley Rat Brain - Shaimi, Asma Ulhusna; Aasim, Wan Raihana Wan; hmad, Wan Amir Nizam Wan A; Abdullah, Hasmah (Proceeding International Conference on Science and Engineering, 2020)
Motorized stereotaxic is an advanced tool for surgery and implantation of cannula and electrodes in neuroscience. Stereotaxic surgery and implantation has become increasingly important tool, applied in many experiments. The goal in this present study to determine the surgical implantation and probe insertion at the target location accurately and precisely using motorized stereotaxic. In this study, the method allowed to evaluate the DHEAS fluorescence level through in vivo imaging approach at the target region in the hippocampus rat brain. This present study also described the surgical implantation and probe insertion by motorized stereotaxic as the precise and accurate techniques than conventional stereotaxic procedures. With the rat brain atlas by Paxinos and Watson (2004), the imaging approach can be evaluated precisely at the target location corresponding surgical implantation and probe insertion techniques.